Dinámica de las adaptaciones morfofuncionales provocadas por la actividad física aeróbica en adultos sedentarios (2018)
Physical activity in sedentary adults is a topic that is passionate and growing every day in the field of exercise science. The therapeutic intervention of physical exercise to rehabilitate or maintain health, has millennial validity and, more today, that humanity faces the combination of factors such as sedentary lifestyle, physical inactivity and bad eating habits.